ANALISIS KADAR OSTEOKALSIN SERUM OSTEOPENIA DAN OSTEOPOROSIS - N Sennang AN; Mutmainnah Mutmainnah; RDN Pakasi; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
Osteoporosis is a metabolic bone disease, characterized by decreased of bone mass density. Its incidence is higher in older population.Serum osteocalcin level is related to the rate of bone turnover. To analyze serum osteocalcin level on osteopenic and osteoporosis subjects.We examined 61 subjects for detecting osteopenia and osteoporosis by Sahara densitometer and measuring serum osteocalcin level byElecsys N-MID Osteocalsin Assay test. Of 21 men and 40 women, prevalence of osteopenia and osteoporosis were higher in women(57.5% and 32.5%) than men (42.9% and 23.8%). Most of osteoporosis subjects were in ≥ 60 years group and osteopenic subjects werein 50–59 years group (p<0.05). Mean of serum osteocalcin on osteoporosis subjects (26.70 ng/mL) was higher than osteopenic (23.78ng/mL) and normal (19.16 ng/mL) subjects (p<0.005). Prevalence of osteopenia and osteoporosis were higher in women than men. Theincidence of osteoporosis was related to the increase of age. Serum osteocalcin level was related to the severity of diagnosis category.